Band alignment and enhanced photocatalytic activation of α/β-Bi2O3 heterojunctions via in situ phase transformation1. Issue 17 (7th May 2015) - Shan, Lianwei; Wang, Guilin; Li, Dan; San, Xingyuan; Liu, Lizhu; Dong, Limin; Wu, Ze
<x xml:space="preserve">Abstract</x> The α/β-Bi2O3 heterojunction prepared by an in situ phase transformation technique shows effective band alignment and high photocatalytic activity.